Maternal and Infant Health Consequences of Polybrominated Diphenyl Ethers (PBDEs) Exposure in Pregnancy - Begum, Myeesha (Université d'Ottawa / University of Ottawa, 2023)
Background: Polybrominated diphenyl ethers (PBDEs) are persistent flame retardants that are found in the environment. Several reports on PBDEs focus on biomonitoring of these chemicals. However, less is understood in terms of PBDE exposure-related adverse effects in vulnerable populations such as mothers and their neonates. Previous toxicology studies indicate that PBDEs display endocrine disrupting properties. This work aimed to investigate the effect of PBDE on adverse pregnancy outcomes and determine an understanding of related maternal toxicity mechanisms with effect biomarkers. Methods: A systematic review was conducted where articles were collected from four different databases: PubMed, Scopus, Embase and Web of Science. A total of 54 articles that met the inclusion criteria were included from the period of January 2005 and February 2022. Results: There were 7 studies on maternal outcomes, 29 articles for birth outcomes and 18 on effect biomarkers. There were consistencies in the direction of association between PBDE exposures in pregnancy and risk of gestational diabetes, gestational hypertension, and pre-eclampsia based on the few studies in this review. Maternal PBDE level was implicated in preterm birth and fetal growth restriction. Most studies found a negative trend in correlation with birth weight, birth length and head circumference. BDE-28 was a common congener to be associated in a decrease in birth length. Studies on thyroid hormones were inconsistent but it was observed that BDE-47 was predominantly associated with a decrease in the relationship. Conclusion: The findings from the systematic review demonstrated consistent evidence of the association between PBDEs and adverse pregnancy health outcomes, while others showed inconsistencies. Differing study qualities may have contributed to these findings. More studies are warranted to validate the findings with larger sample sizes and longitudinal study designs.
Keywords: Polybrominated diphenyl ether; Pregnancy; Maternal; Birth; Biomarkers